GPS Solutions - GPS Solutions (Springer Nature, 2026)
GPS Solutions is a quarterly scientific journal covering system design issues and a full range of current and emerging applications of global navigation satellite systems (GNSS) including GPS, GLONASS, Galileo, and BeiDou.
FI 0.91
Q1
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Aviación; Topografía; Cartografía